Biting Back at Malaria – Self-Medication, Traditional Healers, and the Public Sector - Alfredo R. Paloyo; Arndt R. Reichert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Malaria kills about 1,500 children every day. Based on the Demographic and Health Surveys, we examine malaria treatment practices of various health care providers in sub-Saharan Africa, where more than 90 percent of the world's deaths due to malaria occur. To assess the quality of each health care provider (including, among others, public health centers and traditional healers), we estimate the likelihood of providers to administer ineffective antimalarial drugs such as chloroquine in areas of known resistance, and to relieve children of malaria symptoms after having had fever within the last two weeks. Our results indicate that relative to self-medication, seeking treatment at most providers significantly increases the likelihood to take any antimalarial drug and decreases the likelihood to use chloroquine. Traditional healers do not exert any effect. – – Durch Malaria sterben täglich etwa 1500 Kinder. In dem vorliegenden Artikel werden DHS (Demographic and Health Surveys)-Daten ausgewertet, um die Malariabehandlungspraxis verschiedener Leistungserbringer in Subsahara-Afrika zu vergleichen. Zur Untersuchung von Qualitätsunterschieden zwischen den Anbietern (öffentliche medizinische Versorgungszentren, traditionelle Heiler, etc.) werden die Wahrscheinlichkeiten geschätzt, dass unwirksame Malaria-Medikamente wie Chloroquin in Gebieten mit bekannter Chloroquin-Resistenz verabreicht werden und dass Kinder mit einer Fieberepisode in den vergangenen zwei Wochen keine Malaria-Symptome mehr haben. Die Ergebnisse zeigen, dass das Aufsuchen der meisten Gesundheitsleistungsanbieter die Wahrscheinlichkeit der Einnahme von (wirksamen) Malaria-Medikamenten im Vergleich zur Selbstbehandlung signifikant erhöht und die Wahrscheinlichkeit der Einnahme von Chloroquin signifikant verringert. Das Aufsuchen eines traditionellen Heilers hingegen bleibt wirkungslos.
Keywords: I11; I14; O15; O57; 330; quality of care; health care providers; health inequalities; malaria; sub-Saharan Africa; child health